(untitled) (Scientific journal of the Fergana State University, 2026)
This article presents the results of a study on the geometric and energy parameters of betulinic acid. The research utilized Avogadro, HyperChem, and ChemOffice software, as well as modern approaches such as DFT, MD, QSAR, and molecular docking. The calculations determined formation energies, bond lengths, differences in electronic structure parameters, and the degree of molecular stability. The obtained results reveal promising prospects for the application of betulinic acid in pharmaceuticals and nanomaterials.